Madrasah Diniyah Awaliyah (MDA): A Review of the Value of Religiousness - Muhammad Fikri Riyanto; Khoirunnisa Riani; Mei Ega Yovida Rahayu; Annisa Muhidatun Hasanah; Dimas Rizqi Fajar; M. Hirza Qusuma Dani; Irman Said Prastyo (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
Education is the initial access in the formation of community values, and the study concluded that Islamic education will shape character through the habituation of positive activities. In achieving the goals of national education, namely shaping and building students to make children with character. Through madrasah, Islamic educational institutions carry out the tasks of adaptation, goal achievement, integration, and maintenance of patterns in the implementation of Islamic education both in formal and non-formal schools such as MDA. This type of research is descriptive qualitative. The research was conducted at Madrasah Diniyah Awwaliyah in Ngampel Wetan village, Ngampel sub-district, Kendal district. The data collection process consists of observation and documentation. The results of this study indicate that the existence of Madrasah Diniyah Awaliyah (MDA) will certainly have a positive effect on the religiosity value of students, especially those in Ngampel Wetan Village, Ngampel District, Kendal Regency such as religious beliefs, worship, religious knowledge, religious appreciation, experience or effect